The Role of Awareness, Motivation and Capability on the Competitive Reaction of Middle and Lower Managers of Private Higher Education - Sukaris Sukaris; Heru Baskoro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The dynamics of competition has had an important impact on organizational activities on rival responses and organizational performance, however the inputs that influence the organization's activities, in particular the extent to which the organization reflexively repeats previous activities versus selective taking actions in bundling its strategic framework. The main objective of this study was to determine the competitive reaction of middle managers and lower managers of private universities through awareness, motivation and capability (AMC). Data were obtained from middle and lower managers in private universities. The data that has been collected is tested for validity and reliability and then analyzed using a qualitative response regression model (linear probability model). The results of the validity and reliability have met all the required criteria. The results showed that awareness had a significant positive effect on the possibility of competitive reactions, motivation had an insignificant negative effect on the possibility of competitive reactions and capability had an insignificant positive effect on the possibility of competitive reactions of middle managers and lower managers of private universities.